Occupational Health and Safety Integration in Digital-Based Governance to Support Excellence Campus - Risdianto Risdianto; Wiwi Hartati (MASI Mandiri Edukasi, 2026)
Occupational Safety and Health (OHS) is an essential component of effective university governance. This study aims to examine the implementation of OHS, the utilization of digital governance, and the gap between actual conditions and expectations within the academic community. A quantitative survey was conducted using a 28-item Likert-scale questionnaire administered to 38 student respondents at the University of Muhammadiyah Cirebon. Data were analyzed using descriptive statistics, and the gap was calculated as the difference between the mean scores of expected outcomes and actual conditions across variables. The results indicate that OHS implementation and governance are categorized as good (mean = 3.80), while the utilization of digital OHS systems shows the lowest mean score (3.78), and support for a superior campus records the highest mean score (4.03). A gap of 0.25 was identified, particularly in the digitalization aspect of OHS. These findings suggest the need for strengthening the integration of digital OHS systems to improve safety management in higher education, although the results are limited to the context of the studied institution.